ANALISIS PENERAPAN INTERNATIONAL SHIP AND PORT FACILITY SECURITY (ISPS) CODE DI KM. LEUSER - Tiara Zahra; Bayu Yudho Perkoso; Rizal Rochmansyah; Elfira Wirza; Rosnani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The ISPS Code is a mandatory global standard aimed at mitigating maritime security risks, including Threats of terrorism and criminal activities on board ships. Although this regulation has been implemented, the increasing number of theft cases involving technical inventory and passengers’ belongings on vessels in Indonesia, including a theft incident on MV. Leuser in October 2025, indicates existing gaps in security procedures and monitoring controls while the ship is sailing and when it is berthed at high-risk ports. This study employed a descriptive qualitative method, with data collected through interviews, observations, and documentation. The data were analyzed using SWOT analysis to examine the Strengths, Weaknesses, opportunities, and Threats in the implementation of the ISPS Code on MV. Leuser.. The results show that the implementation of the ISPS Code on MV. Leuser complies with international standards, as reflected in the approved Ship Security Plan (SSP), restricted access to sensitive areas, gangway inspections, and the integration of surveillance systems. However, several technical Weaknesses were identified, including areas not covered by CCTV, insufficient nighttime lighting, and internal communication disruptions. Optimization efforts include strengthening coordination with port authorities and security agencies, utilizing more advanced surveillance technology, improving lighting facilities, and enhancing the quality and variation of Crew training.